PERAN PERAN MEDIA SOSIAL DALAM PEMBENTUKAN NARASI AGAMA ISLAM DI KALANGAN GENERASI Z - Habiba Mafaza Zein; Nisa Nuraini Mardiya (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
Utilization of technology Artificial Intelligence (AI) in education has become increasingly popular in recent years. This study was conducted to determine how AI can improve student achievement in the Islamic Religious Education (PAI) learning process through creative learning that can increase student engagement. The research method used was field research, located at Rambah Middle School. The data source for this study was eighth-grade students discussing the use of AI in creative learning. Data collection techniques were carried out through observation, interviews, and data reduction. Data analysis was carried out by analyzing and synthesizing the collected data to determine the use of AI in creative learning. The results of the study indicate that the use of AI in creative learning in Islamic Religious Education can increase student engagement and achievement in a more effective and efficient manner through projects and assignments using technology. AI can help improve students’ ability to understand learning materials, develop skills, and increase learning motivation during independent learning. In addition, AI can also assist teachers in developing curricula that are appropriate to students' needs and abilities. Thus, the use of AI in creative learning can be one solution to improve the quality of education in Indonesia and help students achieve better performance